THE PREVALENCE OF HYDATIDOSIS IN RUMINANT OF DIFFERENT IRAQI REGIONS - KHUDHUR, HUSSEIN B.; ABDULAZEEZ ALI, MOHAMMED (International Journal of Psychosocial Rehabilitation, 2020)
A retrospective studycovered the period of 10-year (2000-2010) to investigate the prevalence of hydatidosis in ruminantsofthree provinces abattoirsinIraq (Al Muthanna, Al Qadysiah and Al Najaf). A total of 923391 animals including 424167 sheep, 163070 goats, 264351cow, 33133 buffalo and 38670 camel, inspected macroscopically for hydatidosis in 10-year period, out of which9909, 2250, 6387, 740 and 414 respectively were infected with hydatidosis. The incidence of the diseaseinall slaughtered animals varied according to the province, but in general, Al Muthanna province recorded the highest incidence among all slaughtered species followed by Al Qadysiah then Al Najaf province. Buffalo recorded the highest incidence percentage (5.5%)in Al Muthanna and sheep (3.8%) in AlQadysiah while in AL Najafcow showed the highest incidence (2.1%). The current results provide a baseline data for the prevalence of this parasitic disease in these three provinces and its incidence among different species of ruminants, which provide the opportunity for future monitoring and evaluation leading to control programs of hydatid cyst in Iraq.